(3UMjM eSde ,Ch, GdeSei GdefgGL TQM UMjM eSde Hf GdMLGL (B.s - (3Gdfhhj, jMji Hf TQa Hf eQj,s 631-676 (3g`(B.s; (3TjMG , Ndjd eCehf (B.s ((3dHfGf (B:s (3OGQ GdeYQaI ddWHGYI hGdfTQ ,s, 2006)
(3JHOC ef cJGH GdMjV Edi CKfGA cJGH GdLfGFR(B.s
(3GdCOGI GdJhKjbjI (B: (3cTa GdXfhf, eL(B. 1(3, U(B. 555(3, eL(B. 2(3, U(B. 1878-(3eOGNd GdeDdajf, U(B. 592-(3GdCYdGe, eL(B. 8(3, U(B. 149-(3eYLe GdeWHhYGJ, eL(B. 2(3, U(B. 1879.s
(3ejcQhajde(B.s
(3ecJHI CHj GdYHGS GdeQSj ;s
(3GdeNWhWI eWHhYI(B.s
Keywords: (3UMjM eSdes; (3GdMOjKs -- (3TQMs